Enhancing wear resistance in blanking and punching of stainless-steel sheets under dry friction and solid lubrication conditions using single-layer ceramic- and carbon-based hard coatings - Ibrahim, Muhammad Shuhaimi; Sulaiman, Mohd Hafis; S. Ismail, Mohd Idris Shah (Mytribos, 2024)
Punching and blanking encounter challenges in separating tool and workpiece surfaces due to the formation of highly active virgin material, negatively impacting tool surfaces and product quality. To prevent this issue, hard coatings are applied to the tool surfaces. In this study, the wear severity of ceramic-based (TiN and TiAlN) and carbon-based (DLC) coatings deposited on punches during blanking and punching under dry friction and solid-form graphite lubrication were evaluated and compared with uncoated punches. The experiments were performed on 1-mm AISI304 stainless steel sheet thickness at room temperature. The findings indicate that there were no significant differences in force and wear measurements when using all test coatings in dry friction conditions. However, when applying a thin layer of TiN ceramic coating on the tool surface and using solid graphite lubrication, it effectively protected the tool and reduced punching force by 7. This combination also improved wear resistance in the shearing zone, resulting in an extended tool service life and enhanced surface finish.